'Then she got a spanking': Social accountability and narrative versions in social workers' courtroom testimonies. (October 2018) - Franzén, Anna; Aronsson, Karin
Courtroom talk in child custody interrogations recurrently features contrasting event descriptions about 'what happened', as well as contrasting person descriptions. This case study – from a large set of audio-recorded courtroom examinations – documents how social workers' contrasting narrative versions about alleged domestic violence are related to divergent problem formulations. Blame-account sequences feature descriptions of a particular event as violent or nonviolent and descriptions of a new partner as 'non-adult' or merely as 'impulsive' but 'concerned'. Other contrasting person descriptions feature a target child either as 'normal' or as someone who 'has a diagnosis'. This involves categorizations of the particular child either as a victim ('normal child') or as someone 'with a diagnosis', two contrasting accounts that provide divergent explanatory formulations of what the overall problem is. Ultimately, divergent testimonies also reflect how social accounts in court reflect both mitigated/aggravated descriptions of violence and divergent accounts of parents' and children's agency and accountability.